The effect of macroeconomic instability on earnings management in developed versus emerging countries - Viana Junior, D. B. C.; Lourenço, I. M. E. C.; Martins, O. S. (XIX USP International Conference in Accounting, 2019)
This study analyzes the effect of macroeconomic instability on both accrual-based and real earnings management, explicitly examining how this relationship compares between developed and emerging countries. The empirical study relies on a worldwide sample of 92,501 firm-year observations from 38 countries. Based on several variables related to economic environment conditions, we construct a macroeconomic instability index for each analyzed country, which change over the years. Econometric models are estimated using Ordinary Least Squares (OLS) approach, controlled for industry and year fixed effects. Our findings suggest that high levels of macroeconomic instability mitigate accrual-based earnings management in developed economies, whereas it encourages earnings manipulation by accruals in emerging ones. Findings also indicate a trade-off between accrual-based and real earnings management, but only in emerging countries. Overall, this study adds to the literature on the effect of economic environment on accounting quality and fills a gap in the previous literature focused on financial crises, by addressing macroeconomic instability for each year and country and broadening the discussion in different institutional contexts.